Attitude and knowledge towards prescription of generic drugs: online study across Telangana - Sen, Sumana; Bandari, Naveen Kumar (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Generic drugs are similar in terms of strength, safety and therapeutic benefit as compared to innovator counterparts. Generics have a favourable financial profile and a positive effect on medication adherence. Palpable change was not observed with the use of generics. This study has been designed to gauge the knowledge and attitude concerning generic drugs among medical students in their 5th semester of MBBS course and interns in the final six months of their compulsory rotatory residential internship (CRRI) program in the state of Telangana. Methods: It was a cross sectional, online-questionnaire based study across medical colleges in Telangana. The questions were designed with the help of Google forms and the website links were circulated to the participants through students and interns’ whatsapp groups. Results: 95.1% of interns and 92.7% of students had knowledge of generic drugs. Significant number of students had a notion that brand drugs are for serious illnesses. Majority in both the groups maintained a neutral opinion when it came to mandatory prescribing of generics. Conclusions: Our study revealed a similar knowledge level about generic in both the groups and 40.9% of interns and 41.4% of students had a knowledge score of more than or equal to 80. Interns didn’t agree with incentivisation of brand drugs. 37.9% of interns and 32.3% of students had an attitude score of more than or equal to 80. Therefore implementation of certain practices like stocking of more generics at medical college pharmacies, more research and incentivisation of generic use can translate into a rise of generic usage.